A simple and cost-effective real-time PCR method using diluted and heat-treated whole blood lysate - Gökçe Güllü Amuran; Büşra Polat; Abdülkadir Kahraman; Mustafa Akkiprik (Scientific Reports)
Abstract Although DNA extraction is a crucial step before polymerase chain reaction (PCR), attempts to perform PCR without DNA isolation have been ongoing since the 1990s. While partial success has been achieved with direct conventional PCR, the DNA isolation step has remained indispensable for real-time PCR. Here, we developed a method that does not require complete DNA isolation by lysing EDTA-treated whole blood samples through the application of osmotic pressure and heat, followed by centrifugation to get a clear lysate. Blood samples were mixed with distilled water, incubated at 95 °C for 20 min before centrifugation at 14,000 rpm for 5 min. The resulting lysates were used as templates for real-time PCR. Real-time PCRs were performed under identical conditions with lysates and DNA samples using 9 different primer sets. Target genes were successfully amplified using 1:10 and 1:5 diluted blood lysates both at 60 °C and 61 °C. The PCR efficiency for ACTB and PIK3CA differed by 20% and 14%, respectively, between the DNA samples and blood lysates. We successfully amplified all selected genes using “GG-RT PCR”, greater temperature, greater speed method, without the need for additional enzymes or buffers. GG-RT PCR presents a cost effective option for applications such as SNP analysis and deletion detection if appropriate primer designs are made.